Incidence and Knowledge of Hypoactive Sexual Desire Disorder and Its Treatment: A Survey [6Q]. (May 2018) - Phillips, Nancy; Bachmann, Gloria A.; Yeung, Percy; Lu, Chi-Wei
Abstract : INTRODUCTION: HSDD has been recognized as a sexual disorder since 1950. Low sexual desire is self-reported by approximately 40% of women, with the true disorder present in about 14%. Despite this, studies consistently show women being hesitant to discuss sexual issues with their physicians. Women may feel low desire is a normal result of aging, or are unaware of possible treatment. Treatments for HSDD include identification and treatment of secondary causes, counseling or sex therapy, or most recently, flibanserin, FDA approved in 2015. METHODS: An IRB approved survey on HSDD was distributed to women aged 18 and over presenting to a general gynecology practice. The aim of the survey was to gather information on the incidence of decreased sexual desire, knowledge that HSDD was considered a medical diagnosis and assess if women were aware of treatment options. RESULTS: One hundred and thirty-three women participated in the survey. 29% reported decreased desire and 50% of these women reported distress, for a 14.5% incidence of HSDD. However, only 22% of respondents were aware that HSDD was a medical condition and only 12% were aware of an FDA approved medication for it. CONCLUSION: HSDD, by definition, causes marked personal or interpersonal distress. Yet women are not aware that this is a recognized medical condition. As even less women are aware that treatment options exist, even those who would consider discussing this with their physician may be hesitant to do so. Better education of both patients and physicians will help to better serve this unmet need.